2013
DOI: 10.1097/mlr.0b013e3182763230
|View full text |Cite
|
Sign up to set email alerts
|

Person-centered Care Practices and Quality in Department of Veterans Affairs Nursing Homes

Abstract: Our results indicate that culture change to a PCC model is associated with higher Minimum Data Set-based quality. Longitudinal data are needed to better assess whether there is a causal relationship between the extent of culture change and quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 13 publications
0
41
2
Order By: Relevance
“…27 Additionally, upon introduction of culture change, these NHs had a significant decrease in the proportion of residents with pressure ulcers and a small but marginally significant decrease in hospitalizations per resident year. With regard to pressure ulcers, a large study of Dutch NHs similarly found development of a resident council, which is an artifact of culture change, along with implementation of other quality initiatives, was associated with significant reduction in pressure ulcers.…”
Section: Discussionmentioning
confidence: 98%
“…27 Additionally, upon introduction of culture change, these NHs had a significant decrease in the proportion of residents with pressure ulcers and a small but marginally significant decrease in hospitalizations per resident year. With regard to pressure ulcers, a large study of Dutch NHs similarly found development of a resident council, which is an artifact of culture change, along with implementation of other quality initiatives, was associated with significant reduction in pressure ulcers.…”
Section: Discussionmentioning
confidence: 98%
“…These initiatives were generally designed to foster homelike environment in nursing homes, residents’ quality of life, individualized care, and engagement of residents and families, all embraced as essential components of the “Cultural Change” movement in nursing homes (Koren, 2010; White et al, 2012; Sullivan, Shwartz, Burgess, Pekoz, and Christiansen et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Nursing home structural characteristics (e.g. profit status) (Hillmer et al 2005) and philosophical orientation (Grabowski et al 2014; Sullivan et al 2013) have been linked to quality. Higher quality has been linked to lower CNA turnover and absenteeism (Castle, Engberg, and Men 2007) which could impact staffing practices.…”
Section: Discussionmentioning
confidence: 99%